2015
DOI: 10.1089/neu.2013.3321
|View full text |Cite
|
Sign up to set email alerts
|

A Consistent, Quantifiable, and Graded Rat Lumbosacral Spinal Cord Injury Model

Abstract: The purpose of this study is to develop a rat lumbosacral spinal cord injury (SCI) model that causes consistent motoneuronal loss and behavior deficits. Most SCI models focus on the thoracic or cervical spinal cord. Lumbosacral SCI accounts for about one third of human SCI but no standardized lumbosacral model is available for evaluating therapies. Twenty-six adult female Sprague-Dawley rats were randomized to three groups: sham (n=9), 25 mm (n=8), and 50 mm (n=9). Sham rats had laminectomy only, while 25 mm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 86 publications
(92 reference statements)
0
12
0
3
Order By: Relevance
“…BBB might not be applicable to determine the locomotor function for an injury at the thoracic level. One study that created a contusion injury in the lumbosacral region revealed that no behavioral changes could be assessed by BBB scores [ 62 ]. Further, the BBB score focuses on joint movement, weight-bearing, coordination between limbs, postural view, and the positions of the tail and feet [ 43 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…BBB might not be applicable to determine the locomotor function for an injury at the thoracic level. One study that created a contusion injury in the lumbosacral region revealed that no behavioral changes could be assessed by BBB scores [ 62 ]. Further, the BBB score focuses on joint movement, weight-bearing, coordination between limbs, postural view, and the positions of the tail and feet [ 43 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies using the rat SCI model appear to overlook the use of postoperative analgesia, considering the lack of reporting of the use of analgesic regimens in many publications describing this model [31,32,33,34,35]. Where analgesic regimen is reported, variable dosages and durations of administration of analgesics are described, such as acetaminophen 65 mg/kg orally, only if the rat shows the sign of self-mutilation [36]; buprenorphine 0.3mg/kg once daily s/c for two postoperative days [37]; 1.5 ml (0.006 mg/ml) buprenorphine twice daily subcutaneously for first 24–48 hours [38]; and buprenorphine 0.01mg/kg b.i.d.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists are continuously looking for models that resemble the human injuries more closely. For example, two recent studies focused on lumbosacral SCI, a type of injury affecting an estimated one-third of patients [24,25]. A model combining SCI and traumatic brain injury was recently introduced, because a proportion of SCI patients additionally suffer from head injuries, for example, due to traffic or diving accidents [26].…”
Section: New Sci Modelsmentioning
confidence: 99%